Effects of livestock wastewater irrigation on growth, yield, and water and nitrogen use efficiency of garlic - XIANG Meng; LI Ying; HAN Huanhao; CHEN Manyu; LIAO Bin; CUI Yuanlai (Guan'gai paishui xuebao, 2024)
【Objective】 Garlic is a cash crop in Dali, but its irrigation with livestock wastewater risks environmental pollution. This paper studies the combined effect of livestock wastewater irrigation and nitrogen fertilization on growth, yield, water and nitrogen utilization efficiency of garlic, as well as soil nitrogen in attempts to screen a sustainable livestock wastewater irrigation schedule for garlic production in this region. 【Method】 The experiment was conducted at the National Agricultural Environmental Dali Observation and Experimental Station. There were five treatments: freshwater irrigation without nitrogen application (CK), freshwater irrigation with 390 kg/hm2 of nitrogen application (C1), freshwater irrigation with 312 kg/hm2 of nitrogen application (C2), livestock wastewater irrigation without nitrogen application (R1), livestock wastewater irrigation with 150 kg/hm2 of nitrogen application (R2). In each treatment, we measured the growth indexes, including dry weight, height, stem diameter and leaf area index of the garlic at different growing stages, as well as yield, and water and nitrogen use efficiency of the garlic and soil nitrogen content. 【Result】 The growth of the garlic was the best in R2, but was comparable with that in R1 and C1; R2 gave the highest yield. Compared to CK, C1, C2, R1 and R2 increased the bulb yield by 111.30%, 81.23%, 98.19%, and 142.01%, respectively. The nitrogen absorption and use efficiency of R1 and R2 was 154.71% and 92.25% higher than that of C1, respectively; the nitrogen partial factor productivity of R1 and R2 was 110.75% and 47.63% higher than that of C1, respectively. Compared to C1, R1 reduced the irrigation water productivity and soil nitrogen in the 0-40 cm of soil layer by 29.19%, while R2 increased the irrigation water productivity by 2.34% and reduced soil nitrogen in the 0-40 cm of soil by 3.89%, respectively. Compared to C1, R1 and R2 increased nitrogen in the 0-20 cm of soil layer by 170.90% and 255.93% respectively. 【Conclusion】 Livestock wastewater irrigation combined with appropriate base nitrogen fertilization can sustain garlic growth and yield. Livestock wastewater irrigation improved the nitrogen use efficiency and nitrogen partial factor productivity, with limited effect on average soil total nitrogen.